Infidelity as Social Resistance and Class Struggle in Tonnerre’s Lady Chatterley’s Lover (2022) Movie - Nurul Aulia Permana; Nurholis Nurholis; Bunyamin Faisal (MASI Mandiri Edukasi, 2026)
The film Lady Chatterley's Lover (2022) depicts a forbidden relationship within the context of class differences and gender inequality. This study aims to explore how adultery is portrayed as an act of social resistance and how class conflict is revealed in the interactions between Connie Chatterley and Oliver Mellors. This study employs a descriptive qualitative approach with a sociological perspective. Data were drawn from selected scenes and dialogues in the film and analyzed through the lenses of literary sociology, contemporary intimacy theory, and class theory. The results indicate that Connie and Clifford’s marriage is portrayed as an aristocratic institution that stifles emotional intimacy and drives Connie to seek freedom outside it. Her relationship with Mellors not only violates marital norms but also challenges rigid class boundaries. In this context, the affair is seen as both a form of social resistance and an opportunity for personal transformation. This study concludes that the affair in the film functions not only as a violation of norms but also as a reflection of resistance against class structures and social boundaries in modern society.